SAFETY OF BRONCHOALVEOLAR LAVAGE IN HEMATOLOGICAL PATIENTS WITH THROMBOCYTOPENIA – A RETROSPECTIVE COHORT STUDY - Ivan GUR; Roei Tounek; Yaniv Dotan; Elite Vainer Evgrafov; Stav Rakedzon; Eyal Fuchs (Mediterranean Journal of Hematology and Infectious Diseases)
Background